Perancangan dan Pengembangan Produk Kursi Bioskop Menggunakan Metode Quality Function Deployment pada Bioskop - Fitriana Indah Pramitasari; Rossi Septy Wahyuni (Jurnal Informatika Universitas Pamulang, 2021)
A cinema is a movie theater. The development of cinema is very significant both in terms of facilities and technology. These facilities and technology are useful for attracting consumers to watch in the cinema. However, cinema still has problems with audience order. The first problem of order is in the cinema seats. This problem occurs because some spectators do not sit according to the seat number that has been booked on the cinema ticket and are free to move seats so that it can interfere with the comfort of the audience. This problem occurs when the cinema theater seats are not full. The second problem of order is at the theater exit. The problem occurred during the film, some audience members entered the theater through the exit door without paying the ticket in advance because the exit door was not locked and no one was guarding it. The design of the innovative cinema chair product is a cinema chair using an RFID Tag. The method used to design the product is Quality Function Deployment and is described using CATIA software. The customer needs for cinema chairs products are strong cinema chair frames, strong cinema seat foam pads, soft cinema seat fabric/cover, soft cinema seat foam, medium-sized cinema chairs, solid color cinema chairs and additional features of RFID. The technical characteristics of cinema chairs are iron material, wood material, cloth material, foam material, length dimension, width dimension, height dimension, color variation and RFID innovation. Cinema chair product specifications consist of the type of cinema chair material is black powder coating iron, multiplex wood, velvet fabric, foam foam, seat length dimensions of 76 cm, seat width dimensions of 57 cm, seat height dimensions of 110 cm, fabric color is solid and the additional feature is RFID.